Grafting for sustainable management of Fusarium wilt disease in tomato production in Ghana - Awu, J.E.; Nyaku, S.T.; Amissah, J.N.; Okorley, B.A.; Agyapong, P.J.A.; Doku, F.E.; Nkansah, G.O. (Journal of Agriculture and Food Research, 2023)
Fusarium wilt disease limits tomato production, especially in Ghana. In managing the Fusarium wilt disease, two rootstocks (Solanum torvum and Solanum macrocarpon) were used in grafting experiments. Plant growth, yield, disease severity and incidence of both grafted plants, and non-grafted plants were evaluated in a pot experiment and also under a naturally infected open field condition at Berekum. During the early stage (14 days after inoculation) under artificial inoculation conditions, grafted plants exhibited higher photosynthetic rates (10.41 μmol− 2 s − 1 ) compared to the non-grafted plants (8.36 μmol− 2 s − 1 ). Under naturally infested field conditions, chlorophyll content and photosynthetic rate of non-grafted plants decreased. Solanum lycopersicum grafted onto S. macrocarpon and S. torvum were moderately susceptible (20%–40%) to Fusarium oxysporum. However, the non grafted plants were highly susceptible (50%–100%). Yield from the pot experiment for S. lycopersicum grafted onto S. macrocarpon was significantly higher (453.1 g/plant), compared to S. lycopersicum grafted onto S. torvum (350.3 g/plant) and the non-grafted plant (205 g/plant). However, in naturally infected field, the grafted plants increased in fruit yield compared to the non-grafted tomato plants. Solanum macrocarpon and S. torvum as rootstocks offered resistance against F. oxysporum and showed significantly lower disease progression, than the non-grafted plants (P < 0.05). This study revealed that grafting is an effective tool for the management of Fusarium wilt disease and for tomato growth and yield improvement.
Research Article
Keywords: Grafting; Rootstock; Rootstock; Rootstock